Hall effect and magnetic ordering in RB₁₂ - Baranovskiy, A.E.; Grechnev, G.E.; Sluchanko, D.N.; Glushkov, V.V.; Demishev, S.V.; Sluchanko, N.E.; Shitsevalova, N.Yu. (Физика низких температур, 2009)
The concentration of carriers in LuB₁₂ is evaluated theoretically by applying ab initio FP-LMTO calculations. Theoretical results are found to be in agreement with high precision measurements of the Hall RH(T) coefficient which were carried out on single crystals of the rare earth dodecaborides RB₁₂ (R = Ho, Er, Tm, Lu) at temperatures 1.8–300 K. A nature of the antiferromagnetic ordering in RB₁₂ is investigated within the RKKY-like model, which was supplemented by comprehensive electronic structure calculations for paramagnetic, ferromagnetic and antiferromagnetic phases.